نموذج مقترح لدراسة الامن النفسي وعلاقته بالدافعية للانجاز لدى تلاميذ السنة الخامسة ابتدائي - مبروك, وداد (جامعة الوادي - University of Eloued, 2020)
تناولت هذه الدراسة الامن النفسي وعلاقته بالدافعية للانجاز لدى تلاميذ السنة الخامسة ابتدائي، اذ يعد الامن النفسي من الحاجات النفسية الاساسية اللازمة للنمو النفسي والصحة النفسية لكل فرد، ففقدان الامن يؤدي الى احداث خلل في توازن الافراد، اذ ان خبرات الطفولة تلعب دورا هاما في نمو الشعور بالامن النفسي والخبرات الصادمة . وتكرارها والتعرض للمواقف المحبطة والخلافات والصراعات بين الوالدين يؤدي الى انعدام الامن النفسي وهذا بدوره يؤدي الى الكثير من المشاكل النفسية ومن بين هذه المشاكل انخفاض مستوى الدافعية للانجاز، اذ ان الامن النفسي يلعب دورا بالغ الاهمية في الانجاز والابتكار، استهدف البحث الحالي: اولا: قياس الامن النفسي لدى تلاميذ السنة الخامسة ابتدائي ثانيا: قياس الدافعية للانجاز لدى تلاميذ السنة الخامسة ابتدائي ثالثا: التعرف على الفروق في درجة الشعور بالامن النفسي والدافعية للانجاز لدى تلاميذ السنة الخامسة ابتدائي وفق المتغيرات التالية: 1- الجنس(ذكور- اناث) 2- السنة الدراسية(السنة الخامسة ابتدائي) رابعا: التعرف على العلاقة بين الامن النفسي والدافعية للانجاز لدى تلاميذ السنة الخامسة ابتدائي واستلزم تحقيق هذه الاهداف الاعتماد على مقياسين الاول للامن النفسي والثاني للدافعية للانجاز، حيث تم استخراج الصدق والثبات،طبق المقياس على عينة من طلبة المرحلة الابتدائية بلغت 40 تلميذ وتلميذة تم اختيارهم بالطريقة الطبقية العشوائية موزعين وفق متغير الجنس والسنة الدراسية،وتوصل البحث الى النتائج التالية: تلاميذ السنة الخامسة ابتدائي اظهروا مستوى عال من الشعور بالامن النفسي ومستوى عال من الدافعية للانجاز لم يكن هناك فروق دالة احصائيا بين الذكور والاناث في الشعور بالامن والدافعية للانجاز لدى تلاميذ السنة الخامسة ابتدائي وجود علاقة ارتباطية موجبة دالة قوية بين الشعور بالامن النفسي والدافعية للانجاز This study dealt with psychological security and its relationship to motivation for achievement among primary fifth-year student as psychological security is one of the basic psychological needs necessary for the psychological development and mental health of each individual the loss of security leads to disturbing the balance as chidhoom experiences play an important role in developing a sense of psychological security and traumatic experiences and their repetition and exposure to frustrating situations disputes and conflicts between parents leads to psychological insecurity This in turn leads to many psychological problems among these problems is the low level of motivation for achievement as psychological security plays a very important role in achievement and innovation The current research aimed not to Measure the psychological security of fifth-year primary students Second:Measuring the motivation for achievement of the fifth year primary students Third.Identifing the diffrences in the degree of feeling psychological security and motivation for achievement among fifth year pupils according to the following variables Sex(male-female) academic year fifth year beginning Forth: Knowing the relationship between psychological security and motivation for achievement among fifth year pupils and achieving these goals requred relying on two measures the first for psychological security and the second for impulse for achievement where honesty and constancy were extracted The scale was appleid to a sample of primary school students amounting to 40 male and female students who were selected by the random stratified method distributed according to the gender variable and the school year and the research reached the following results beginning fifth year pupils showed a high level of psychological security and a high level of achievement motivation There were no statistically significant differences between males and females in the sense of security and motivation for achievement among fifth year pupils starting with a strong positive correlation between the feeling of psy chological security and motivation for achievement
مقال
Keywords: الامن النفسي، الدافعية للانجاز، المرحلة الابتدائية; psychological security, Motivation for achievement,Primary stage